Mascot Magic or Sporting Spectacle: An Interrupted Time Series Analysis with Social Listening Tools to Assess the Effect of “Butterbear” Mania and the 2024 European Football Championship on the Mental Well-being of Thai Residents - Wongsanuphat, Suphanat; Jitpeera, Charuttaporn; Suphanchaimat, Rapeepong; Norphun, Naruttha; Na-on, Bhornpimon; Thammawijaya, Panithee (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2025)
Mental health is a major public health issue in Thailand. In June and July 2024, a commercial mascot called “Butterbear” and the Euro-2024 football tournament were trending on social media. This study assessed gender, age, and geographic-specific exposure to these trends and their association with mental well-being in Thailand. We applied an interrupted time series analysis to compare mental well-being across gender, age, and region. Data from the Mental Health Check-in, from January 2020–July 2024, were used to estimate the levels of stress and depression, and the risk of suicide. Google Trends and social media analytics provided engagement data. Seasonal autoregressive integrated moving average models with exogenous regressors incorporating socioeconomic indicators were used. Totally, 5,499,170 responses were recorded, with stress, depression, and suicide risk levels at 7.8%, 5.2%, and 9.1%, respectively. “Butterbear” and “Euro-2024” were searched 631,414 and 1,975,759 times, respectively. Significant female engagement for “Butterbear” and male engagement for “Euro-2024” in the 18–34-year age group were observed. Improvements in mental well-being were found among females in Bangkok aged 18–34 years in terms of stress (−18.0%), depression (−22.8%), and suicide risk (−18.0%) compared to predicted levels. Males and females outside Bangkok, had smaller differences, with changes in stress levels ranging from −4.2% to 5.7%. The study's trends suggest a mental health relationship with these global events, influenced by media marketing. Leveraging popular phenomena such as Butterbear and global sporting events such as Euro-2024 can enhance mental well-being and could be utilized as part of health promotion campaigns.